Efficiency and Productivity Evaluation of the Moroccan Judicial System - Achenchabe, Yassine; Akaaboune, Mohammed (European Scientific Journal, ESJ, 2021)
This paper focuses on measuring the efficiency and productivity change in 110 Moroccan courts between 2013 and 2018, which is the period of implementation of the judicial reform. The study also measures the technical and scale efficiency using the Data Envelopment Analysis method under output orientation. The Malmquist index was used to measure the productivity change decomposed into efficiency and technical change. The results show a low level of courts efficiency of 53.2%, with increasing returns to scale for most courts except administrative ones. The total factor productivity of courts shows an improvement of 6.3%, mainly due to technical change, except for the commercial courts whose productivity deteriorated during the study period. These results show the positive effect of the reform. Courts still have a margin for improving their efficiency by increasing inputs in order to benefit from economies of scale or by improving judges’ productivity.